Environmental impacts integrated assessment of of KwaZulu-Natal Electrification Programme: A case study of Ndumo Gezisa 132/22kV multi-circuit power line KwaZulu-Natal - Darkey, Dan (University of Pretoria, 2019)
Dissertation (MSc)--University of Pretoria, 2018.